LDH levels and left atrial ultrastructural chances in patients with mitral paraprosthetic regurgitation - ERCAN, FERİHA (WILEY, 2005)
Background and aim: The aim of this study was to assess the effect of paraprosthetic regurgitation of mitral mechanical valves to myocardial tissue and lactate dehydrogenase (LDH) level. Methods: We compared 19 patients (study group) who had mitral mechanical valve with severe mitral paravalvular regurgitation with 20 patients (control group) who had native valve with severe rheumatic mitral regurgitation. None of the patients had clinical hemolytic anemia. On transesophageal echocardiographic examination, semiquantative evaluation and spatial distribution of regurgitant jets were noted in both of the groups. Five LDH isoenzymes were studied in two groups. Myocardial tissue specimens were taken from the left atrial wall during reoperation. Grids randomly taken were studied under the transmission electron microscope. Results: Total serum LDH levels of the study group (578 +/- 12 IU/L) were higher than the control group (495 +/- 6.2 IU/L) (p < 0.001). We found LDH1/LDH2 more than 1 in all patients; the ratio was not statistically different in the control group. Electron microscopy revealed the same degree of injury in both groups. Haptoglobin levels were decreased and reticulocyte counts were increased in patients with paraprosthetic valve regurgitation. Conclusions: Electron microscopic findings support that myocardial injury contributes to increase of total LDH level and high LDH1/LDH2 ratio. But statistically significant elevation in total LDH level in study group and the stable state of LDH1/LDH2 ratio between two groups showed that hemolysis caused by paraprosthetic regurgitation is the most important factor for the increase of total LDH level, so that high LDH level can be used as a reliable parameter for the diagnosis of intravascular hemolysis in paraprosthetic regurgitation.
Keywords: VALVE-REPLACEMENT; PARAVALVULAR LEAKAGE; HEMOLYTIC-ANEMIA; ECHOCARDIOGRAPHY; PROSTHESIS; MECHANISMS; SURGERY